Gel casting of large area micro- and sub-micropatterned thin ceramic tapes. Issue 4 (March 2016) - Brandes, Christoph; Megne Tague, Armelle Cathy; Kroll, Stephen; Treccani, Laura; Rezwan, Kurosch
Abstract: In this study an easy-to-use ceramic processing technique based on temperature-controlled ionotropic gelation of alginate is presented. This method is the breakthrough for simultaneously large scale tape casting and high quality patterning of thin ceramic tapes. Alumina powder ( d 50 = 205 nm) is used to cast flexible and on demand shapeable tapes. Compared to conventional ceramic micropatterning, ionotropic gelation combines complexity of the patterned structure over large-scale areas, a high pattern resolution down to sub-µm regime ( 400 nm) and tape thickness below 300 µm. Obtained green and sintered (1350 °C) micro- and sub-micropatterns are characterized by SEM and quantitative 3D-profilometry focusing on both, pattern quality and pattern aspect ratio. The results show that reproducible thin ceramic tapes featuring positive and negative patterns maintain their aspect ratios after demolding, drying and sintering. This processing route represents a versatile tool for designing tailored ceramics for e.g. microelectromechanical engineered systems, biomaterial or microfluidic applications.